Getting Jesus off the altar: Undoing atonement readings in Revelation - Bowden, Anna M. V. (Review and expositor, 2021)
The interpretive history of Revelation is overrun with descriptions of Jesus as a sacrificial lamb. Yet, John never uses the popular phrase to describe him. By drawing attention to four significant omissions in the text, I argue against atonement readings of “the Lamb” in Revelation. Revelation is not a theological treatise on the meaning of the cross. It feeds questions about power and violence and admonishes the seven churches against participation in their imperial context. John’s slaughtered lamb, therefore, does not evoke a paschal sacrifice; it points to Rome’s penchant for violence. Joining the other bloodied bodies in Revelation, the lamb’s blood further incriminates Rome. Everywhere one looks in John’s depiction of empire, violence lurks. Finally, the only altar in Revelation is the heavenly altar, and this altar is not a place for sacrifice. The heavenly altar is a place where the laments of the suffering are heard, a place for worshipping God, and a place where Rome will meet its judgment. John’s Jesus is not a self-sacrificing spiritual savior; he bears witness to the bloodthirsty, massacre-loving beast-of-all-beasts. Churches must choose their allegiance.